Aluminum Filled Polyethylene-based Thermally Conductive High Performance Composites Prepared by Solid State Shear Milling - Wu, He-jun; Lu, Can-hui; Li, Qing-ye; Hu, Biao (Cai liao gong cheng = Journal of materials engineering, 2016)
Solid state shear milling(S3M) followed by melt mixing process was applied to prepare linear low-density polyethylene(LLDPE)/aluminum(Al) composites with high performance. The morphological change of Al particulates during S3M was characterized by scanning electron microscope(SEM) and laser scattering particle analyzer. The thermal conductivity, mechanical properties and thermal stability of the LLDPE/Al composites were investigated. The results indicate that, under the complex combination of shearing, compression, stretching and friction actions, the spherical Al particulates are squeezed into flakes during compounding with LLDPE by S3M, and their dispersion and interfacial adhesion are improved as well, leading to significance properties enhancement of the resulting composites. At 80%(mass fraction) filler loading, thermal conductivity of the composite prepared by S3M for 10 cycles is as high as 8.782W[middot]m super(-1)[middot]K super(- 1), and the tensile strength and flexural strength respectively are 33